2018
DOI: 10.3389/fimmu.2018.01237
|View full text |Cite
|
Sign up to set email alerts
|

Restoring T Cell Homeostasis After Allogeneic Stem Cell Transplantation; Principal Limitations and Future Challenges

Abstract: For several leukemia patients, allogeneic stem cell transplantation (allogeneic-SCT) is the unique therapeutic modality that could potentially cure their disease. Despite significant progress made in clinical management of allogeneic-SCT, acute graft-versus-host disease (aGVHD) and infectious complications remain the second and third cause of death after disease recurrence. Clinical options to restore immunocompetence after allogeneic-SCT are very limited as studies have raised awareness about the safety with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 118 publications
1
19
0
Order By: Relevance
“…Absolute lymphocyte numbers showed a similar trend (Supplementary Table 1). These findings may be explained by the dynamics of T cell reconstitution following allo-HSCT; previous reports have shown that CD8 + T cell numbers recover rapidly after transplantation, whereas CD4 + T cell reconstitution is significantly slower [2,52,53].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Absolute lymphocyte numbers showed a similar trend (Supplementary Table 1). These findings may be explained by the dynamics of T cell reconstitution following allo-HSCT; previous reports have shown that CD8 + T cell numbers recover rapidly after transplantation, whereas CD4 + T cell reconstitution is significantly slower [2,52,53].…”
Section: Resultsmentioning
confidence: 89%
“…Allogeneic hematopoietic stem cell transplantation (allo-HSCT) can eradicate several blood cancers that are otherwise incurable by chemotherapy alone, due in large part to the graft-versus-tumor effect [1]. Despite indisputable successes due to the graft-versus-tumour effect, the efficacy of allo-HSCT is hampered by cancer recurrence and the development of graft-versus-host disease (GVHD) [2,3]. Notably, reducedintensity conditioning in lieu of myeloablative conditioning has improved patient survival following allo-HSCT by attenuating the acute toxic effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, exposure to IL-7, IL-15, or IL-21 during expansion protocols has been shown to preserve a less-differentiated state and improve in vivo persistence (Hinrichs et al, 2008;Russo et al, 2018;Santegoets et al, 2013;Xu et al, 2014). IL-7 has been evaluated to promote lymphoid reconstitution in the setting of stem cell transplant, but precisely how to use this and other g c cytokines most effectively are still under study (Mackall et al, 2011;Moutuou et al, 2018). Because of the critical role for IL-2 in Treg cell homeostasis, IL-2 has also been considered in the treatment of autoimmunity (Sharabi et al, 2018).…”
Section: G C Family Cytokines and Translational Advancesmentioning
confidence: 99%
“…This thymus-independent mechanism is mainly important for early T cell reconstitution, since thymopoiesis takes at least 6 to 12 months to occur. Thymopoiesis is affected by age-related regeneration capacity, therapy-induced cytotoxic insults, stem cell source and GvHD [ 19 , 20 , 21 , 22 ]. This process results in the emergence of novel phenotypically naive T cells that have maturated in the thymus, simultaneously increasing TCR diversity, which is related to a better clinical outcome [ 23 , 24 , 25 , 26 ].…”
Section: T Cell Reconstitution After Allo-hctmentioning
confidence: 99%